WAWASAN KEBANGSAAN KELOMPOK SALAFI DI NUSA TENGGARA BARAT: STUDI KELOMPOK SALAFI DI PONDOK PESANTREN DAARUSY-SYIFAAΓÇÖ (Harmoni, 2014)
The research questions posed in this study are: (1) What are the views of the Salafis in Pesantren Abu Hurairah in Mataram and Pesantren Daarusy Syifaa in Selong on concepts of nationality and Islam, as well as the relationship between these two entities; (2) What is their idea of the ideal form of the Republic of Indonesia, Pancasila, the Constitution of 1945 and the Bhinneka Tunggal Ika (Unity in diversity) view of nation and state; and (3) Do their views on the above disturb or pose a threat to the integrity of national life for Indonesians? This study aims to: (1) Provide a comprehensive overview of Salafi views on the concept of nationality and Islam and the relationship between them; (2) Provide an overview of their views on the concept of the Republic of Indonesia, Pancasila, Constitution of 1945 and Bhinneka Tunggal Ika (Unity in diversity) in the context of the nation in accordance with their ideal state; and (3) Provide an overview of their opinions on the aforementioned four pillars that may be perceived as a threat to the integrity of national life for Indonesians. The results of this study is useful for the Ministry of Religious Affairs and its relevant agencies for the formulatation of some policies for improving teaching in pesantrens on IndonesiaΓÇÖs national framework. For the pesantren leaders concerned, the results of this study are can help enhance Islamic brotherhood, as well nation brotherhood.
Keywords: Islam; Nationality; Salafi; Radicalism; Kebangsaan; Radikalisme